2020
DOI: 10.3389/fimmu.2020.01473
|View full text |Cite
|
Sign up to set email alerts
|

The Hippo Pathway in Innate Anti-microbial Immunity and Anti-tumor Immunity

Abstract: The Hippo pathway responds to diverse environmental cues and plays key roles in cell fate determination, tissue homeostasis, and organ regeneration. Aberrant Hippo signaling, on the other hand, has frequently been implicated in diversified pathologies such as cancer and immune dysfunction. Here, we summarize the recent but rapid progress in understanding the involvement of the Hippo pathway in innate immunity, with a special focus on the intrinsic mechanisms and mutual interactions between Hippo-YAP signaling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 114 publications
0
6
0
Order By: Relevance
“…Though there has been little research on the Wnt signaling pathway in crustaceans, a recent study found that Wnt genes might participate in the immune response of L. vannamei after infection with Staphylococcus aureus , Vibrio parahaemolyticus , and WSSV ( 84 ). The Hippo signaling pathway, originally considered to be a growth regulation pathway, has recently been found to play indispensable roles in the regulation of innate anti-bacterial immunity and anti-viral immunity ( 85 , 86 ). Several studies have demonstrated that both the Wnt signaling pathway and Hippo signaling pathway are involved in intestinal regeneration and intestinal homeostasis ( 87 90 ).…”
Section: Discussionmentioning
confidence: 99%
“…Though there has been little research on the Wnt signaling pathway in crustaceans, a recent study found that Wnt genes might participate in the immune response of L. vannamei after infection with Staphylococcus aureus , Vibrio parahaemolyticus , and WSSV ( 84 ). The Hippo signaling pathway, originally considered to be a growth regulation pathway, has recently been found to play indispensable roles in the regulation of innate anti-bacterial immunity and anti-viral immunity ( 85 , 86 ). Several studies have demonstrated that both the Wnt signaling pathway and Hippo signaling pathway are involved in intestinal regeneration and intestinal homeostasis ( 87 90 ).…”
Section: Discussionmentioning
confidence: 99%
“…e Hippo pathway plays a crucial role in maintaining homeostasis, inflammation-induced regeneration, and innate immunity [40]. In summary, turmeric may have a therapeutic effect on gout through protein processing in the endoplasmic reticulum and HIF-1 signaling pathway, and corn silk may act through the Hippo signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…There is accumulating evidence that YAP1 facilitates the immunosuppressive tumor microenvironment, affecting myeloid-derived suppressor cells, macrophages, and regulatory T-cells ( Shibata et al, 2018 ; Taha et al, 2018 ; White et al, 2019 ). However, the underlying mechanisms by which YAP1 contributes to tumor immunity is not clearly established ( Hong et al, 2018 ; Zhang et al, 2018 ; Wang et al, 2020 ; Zhang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%